Mechanisms of chaperone suppression of polyglutamine disease: selectivity, synergy and modulation of protein solubility in Drosophila. - Chan, H.Y.E.; Warrick, J.M.; Gray-Board, G.L.; Paulson, H.L.; Bonini, N.M. (Human Molecular Genetics, 2000)
At least eight dominant human neurodegenerative diseases are due to the expansion of a polyglutamine within the disease proteins. This confers toxicity on the proteins and is associated with nuclear inclusion formation. Recent findings indicate that molecular chaperones can modulate polyglutamine pathogenesis, but the basis of polyglutamine toxicity and the mechanism by which chaperones suppress neurodegeneration remains unknown. In a Drosophila: disease model, we demonstrate that chaperones show substrate specificity for polyglutamine protein, as well as synergy in suppression of neurotoxicity. Our analysis also reveals that chaperones alter the solubility properties of the protein, indicating that chaperone modulation of neurodegeneration in vivo is associated with altered biochemical properties of the mutant polyglutamine protein. These findings have implications for these and other human neurodegenerative diseases associated with abnormal protein aggregation.